The subduction history of the Paleo-Pacific Oceanic plate from the Mesozoic to early Cenozoic in NE China and Sikhote-Alin, Russian Far East - Liu, Kai (Curtin University, 2021)
The subduction of the Paleo-Pacific oceanic plate in NE China was probably initiated ca. 250 Ma ago. The Mudanjiang Ocean was closed between the Late Jurassic and Early Cretaceous. After that, the roll-back of the Paleo-Pacific oceanic plate and large-scale sinistral strike-slip faulting dominated the tectonics of the NE Asian continental margin. During the early Cenozoic, subduction of the Izanagi-Pacific ridge was subducted extended from SW Japan to Sikhote-Alin.